2014
DOI: 10.3345/kjp.2014.57.7.304
|View full text |Cite
|
Sign up to set email alerts
|

Benign convulsion with mild gastroenteritis

Abstract: Benign convulsion with mild gastroenteritis (CwG) is a type of afebrile seizure that occurs in children. CwG is defined as a convulsion in a previously healthy child with no known central nervous system infection or encephalopathy, accompanying mild diarrhea without fever, electrolyte imbalance, or moderate to severe dehydration. Convulsions in CwG are characterized by multiple brief episodes of generalized or focal seizures. Although the etiology and pathophysiology have yet to be fully explained, many pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 47 publications
(120 reference statements)
6
62
1
Order By: Relevance
“…We defined seizures lasting >10 minutes as PSE. In previous studies, most patients exhibited GT, atonic, tonic, and partial focal seizures with secondary generalization [22][23][24] . Our patients showed GTC, GT, or focal motor seizures.…”
Section: The Duration Of Seizures In Cwg Is Usually 30 Seconds To <5mentioning
confidence: 78%
See 3 more Smart Citations
“…We defined seizures lasting >10 minutes as PSE. In previous studies, most patients exhibited GT, atonic, tonic, and partial focal seizures with secondary generalization [22][23][24] . Our patients showed GTC, GT, or focal motor seizures.…”
Section: The Duration Of Seizures In Cwg Is Usually 30 Seconds To <5mentioning
confidence: 78%
“…Lee et al reported that febrile CwG had clinical features similar to those of febrile seizures and not intermediate between those of CwG and febrile seizure. 12) Febrile seizures usually involve a single seizure, whereas CwG involves multiple seizures in clusters 7,23) .…”
Section: Seizure Characteristics In Children With Practical Status Epmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the patient has symptoms of diarrhea and/or vomiting before or after seizures, this can indicate the presence of benign convulsions with mild gastroenteritis (CwG) . Additionally, if the season is early winter or spring when rotavirus and norovirus are prevalent, CwG have to be considered in patients especially between 13 to 24 months of age with short-lasting seizures (less than 5 minutes) occurring in clusters [3][4][5][6][7][8][9][10][11][12]15,16,19,24].…”
Section: Introductionmentioning
confidence: 99%